2016
DOI: 10.1080/09593330.2016.1198831
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anaerobic degradation of azo dye with riboflavin and nicotinamide adenine dinucleotide harvested by osmotic lysis of wasted fermentation yeasts

Abstract: The study presented here aims at identifying the source of redox mediators (riboflavin), electron carriers nicotinamide adenine dinucleotide (NAD) and carbon to perform decolorization of azo dye under anaerobic conditions after osmotic shock pretreatment of residual yeast from industrial fermentation. Pretreatment conditions were optimized by Doehlert experiment, varying NaCl concentration, temperature, yeast density and time. After the optimization, the riboflavin concentration in the residual yeast lysate (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Considering that yeast extract is source of riboflavin, some studies investigated the applicability of commercial yeast extract to improve color removal in anaerobic reactors (Baˆeta et al, 2012;Corrˆea et al, 2009). More recently, it has been shown that residual yeast (from fermentation processes) pretreated by osmotic lysis led to higher decolorization, when compared with commercial yeast extract, and exhibited color removal efficien-cies higher than those normally reported in the literature, that is, 86% compared with 81% (Victral et al, 2016). This highlights that yeast extract acts as source of redox mediator, as well as a nutrient source.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Considering that yeast extract is source of riboflavin, some studies investigated the applicability of commercial yeast extract to improve color removal in anaerobic reactors (Baˆeta et al, 2012;Corrˆea et al, 2009). More recently, it has been shown that residual yeast (from fermentation processes) pretreated by osmotic lysis led to higher decolorization, when compared with commercial yeast extract, and exhibited color removal efficien-cies higher than those normally reported in the literature, that is, 86% compared with 81% (Victral et al, 2016). This highlights that yeast extract acts as source of redox mediator, as well as a nutrient source.…”
Section: Resultsmentioning
confidence: 91%
“…Residual Yeast. Residual yeast biomass belonging to Saccharomyces cerevisiae, and obtained from a small brewery, was pretreated through osmotic lysis as proposed by Victral et al (2016). To this aim, yeasts were taken directly from the fermentation vats, where the process was already over, and submitted to successive washing centrifugations, with ethanol for clarification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual yeast biomass belonging to Saccharomyces cerevisiae species was obtained from a small brewery pretreated through osmotic lysis [11,12]. For this, yeasts were taken directly from fermentation vats and submitted to a clarification process, which consisted in a sequence of centrifugations and addition of ethanol solution 96% (10% M/M).…”
Section: Residual Yeastmentioning
confidence: 99%
“…For instance, the application of immobilized redox mediators in microbial fuel cells was tested for electricity generation with simultaneous azo dye removal due to facilitated electrons transfer from bacteria to anodes and azo dyes [8]. In this context, the use of low cost redox mediators have been suggested, such as commercial yeast extract (source of riboflavin) [2,9,10] or residual yeast from the brewing industry [11,12]. Dyes are deficient in carbon and nitrogen sources, and the biodegradation of dyes without any supplement of these sources may be hampered.…”
Section: Introductionmentioning
confidence: 99%